ANALISIS LAPORAN REALISASI ANGGARAN PENDAPATAN PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KOTA MEDAN - Nasution, Nina Andriany (ITB AAS INDONESIA, 2024)
This research aims to prepare a Budget Realization Report (LRA) which includes ratios with criteria. The theory used in this research is government accounting standards and the hypothesis proposed is that income variance is unfavorable, regional independence is very good and the effectiveness of PAD is quite effective. That the analytical tool in this research uses a quantitative descriptive method, namely by studying government accounting standards applied in the field so that there are differences with phenomena and the field in the field of the Medan City Regional Financial and Asset Management Agency (BPKAD). Based on the research results, it can be concluded that regional revenues have not been able to obtain revenues exceeding the budgeted amount and have not been able to increase original regional revenues, including revenues. Keywords: Budget Realization Report, Income Analysis and PAD Effectiveness